The significance of space in Iris Murdoch’s "The Unicorn" as a twentieth-century Irish Gothic novel - Jarząb, Joanna (Adam Mickiewicz University, 2014)
During the twentieth century almost all literary genres came back to prominence in different and alternative forms. The Gothic is no exception to this phenomenon as many a writer made an attempt at using this eighteenth-century genre once again, but adding to it some contemporary elements. Consequently, an abundance of new techniques have been introduced to Gothic fiction to evoke the feeling of horror and terror among the more and more demanding readers of modern times. Still, some writers prefer to return to the traditional concept of the Gothic – as does Iris Murdoch in her novel The Unicorn. The purpose of this article is to analyse the text from the perspective of the Irish Gothic. Those features of the genre which are traditional as well as local are going to be discussed in the context of space as the dominating aspect of the novel. The typical Irish landscape abounding in marshes, bogs and the sea will be contrasted with the inner space of the house, and its resemblance to the old Victorian mansions popular among the Anglo-Irish ascendancy of nineteenth-century Ireland. In what follows, the paper aims at showing how Murdoch’s skilful play with the spatial differentiation between the inside and the outside dislodges other more universal issues, such as the question of freedom, of social taboos and of the different anxieties still present in Irish society today.
Keywords: Irish fiction; Iris Murdoch; Gothic; big house novel